Clinical characteristics of Ureaplasma urealyticum infection and colonization in extremely preterm infants - Wang, Yan-Qiong; Zeng, Ya-Li; Chen, Xue-Yu; Huang, Zhi-Feng; Yang, Chuan-Zhong (Zhongguo dang dai er ke za zhi, 2024)
To investigate the clinical characteristics of (UU) infection and colonization in extremely preterm infants and its impact on the incidence of bronchopulmonary dysplasia (BPD). A retrospective analysis was conducted on 258 extremely preterm infants who were admitted to the Department of Neonatology, Shenzhen Maternity and Child Healthcare Hospital, from September 2018 to September 2022. According to the results of UU nucleic acid testing and the evaluation criteria for UU infection and colonization, the subjects were divided into three groups: UU-negative group (155 infants), UU infection group (70 infants), and UU colonization group (33 infants). The three groups were compared in terms of general information and primary and secondary clinical outcomes. Compared with the UU-negative group, the UU infection group had significant increases in the incidence rate of BPD, total oxygen supply time, and the length of hospital stay ( <0.05), while there were no significant differences in the incidence rates of BPD an